Sorption of cadmium onto Mg-Fe Layered Double Hydroxide (LDH)-Kiwi branch biochar. Issue 1 (1st January 2019) - Tan, Yuehui; Yin, Xianqiang; Wang, Caiyun; Sun, Huimin; Ma, Aisheng; Zhang, Guilong; Wang, Nong
ABSTRACT: The Cd(II) adsorption of kiwi biochar functionalized with Mg-Fe (3:1) layered double hydroxides (LDH) was studied. And the biochar was got via liquid-phase deposition, by incorporating Mg-Fe layered double hydroxide (Mg-Fe LDH) particles into kiwi biochar (KB/LDH). The batch of sorption experiments were studied, including adsorption kinetics and isotherm and the effects of pH, ion strength (IS) and co-existing ions. The KB/LDH composite showed a strong sorption ability to Cd(II) in aqueous solutions with the adsorption capacity of 25.6 mg g −1, compared with pristine biochar of 1.78 mg g −1 . The adsorption of Cd(II) on KB/LDH composite increased with the decreasing of IS, decreased first and then grew larger with the increase of pH and was observed irrespective of the co-existence of K +, Cl − and NO3 − . To sum up, the KB/LDH can be potentially used as an alternative adsorbent to amend the water and soil contaminated by Cd(II).